Voice Control in Calorie Tracker Application using Levenshtein Distance Algorithm - Daniel Halim; Seng Hansun (Aceh International Journal of Science and Technology, 2018)
Each food consumed by people contains a number of calories needed by the body to perform an activity. Calories can be described as fuel of engine to move and carry out tasks. Public’s indifference to the food consumed can cause some negative effects on health like, too skinny, obesity, and emergence of various diseases. Therefore, it is necessary to have an application which can provide some information about the calorie needs, so that user can control the calorie intake. This paper describes the development of an application to assist user in controlling calorie intake according to the calorie needs. This application supports voice control feature to improve user comfort in performing certain commands and inputting food consumed. In addition, this application also uses Levenshtein Distance algorithm to correct food recognition errors which is spoken by user. This application is developed using Java programming language for Android with SQLite database.